Do Nurses Provide a Safe Sleep Environment for Infants in the Hospital Setting? An Integrative Review. (February 2015) - Patton, Carla; Stiltner, Denise; Wright, Kelly Barnhardt; Kautz, Donald D.
Abstract : Background: Sudden infant death syndrome (SIDS) may be the most preventable cause of death for infants 0 to 6 months of age. The American Academy of Pediatrics (AAP) first published safe sleep recommendations for parents and healthcare professionals in 1992. In 1994, new guidelines were published and they became known as the "Back to Sleep" campaign. After this, a noticeable decline occurred in infant deaths from SIDS. However, this number seems to have plateaued with no continuing significant improvements in infant deaths. Objectives: The objective of this review was to determine whether nurses provide a safe sleep environment for infants in the hospital setting. Research studies that dealt with nursing behaviors and nursing knowledge in the hospital setting were included in the review. Data Sources: A search was conducted of Google Scholar, CINAHL, PubMed, and Cochrane, using the key words "NICU, " "newborn, " "SIDS, " "safe sleep environment, " "nurse, " "education, " "supine sleep, " "prone sleep, " "safe sleep, " "special care nursery, " "hospital policy for safe sleep, " "research, " "premature, " "knowledge, " "practice, " "health care professionals, " and "parents." Study Eligibility Criteria: The review included research reports on nursing knowledge and behaviors as well as parental knowledge obtained through education and role modeling of nursing staff. Only research studies were included to ensure that our analysis was based on rigorous research-based findings. Several international studies were included because they mirrored findings noted in the United States. All studies were published between 1999 and 2012. Participants: Healthcare professionals and parents were included in the studies. They were primarily self-report surveys, designed to determine what nurses, other healthcare professionals, and parents knew or had been taught about SIDS. Synthesis Method: Integrative review. Results: Thirteen of the 16 studies included in the review found that some nurses and some mothers continued to use nonsupine positioning. Four of the 16 studies discussed nursing knowledge and noncompliance with AAP safe sleep recommendations. Eleven of the 16 studies found that some nurses were recommending incorrect sleep positions to mothers. Five of the 16 studies noted that some nurses and mothers gave fear of aspiration as the reason they chose to use a nonsupine sleep position. Limitations: In the majority of the studies, the information was self-reported, which could impact the validity of the findings. Also, the studies used convenience sampling, which makes study findings difficult to generalize. Conclusions and Implications: The research indicates that there has been a plateau in safe sleeping practices in the hospital setting. Some infants continue to be placed in positions that increase the risk for SIDS. The research also shows that some nurses are not following the 2011 AAP recommendations for a safe sleep environment. Clearly, nurses need additional education on SIDS prevention and the safe sleep environment, and additional measures need to be adopted to ensure that all nurses and all families understand the research supporting the AAP recommendation that supine sleep is best. Further work is needed to promote evidence-based practice among healthcare professionals and families.